Ethical Considerations in Ever-Expanding Utilization of ECLS: A Research Agenda - Clark, Jonna D.; Baden, Harris P.; Berkman, Emily R.; Bourget, Erica; Brogan, Thomas V.; Di Gennaro, Jane L.; Doorenbos, Ardith Z.; McMullan, D. Michael; Roberts, Joan S.; Turnbull, Jessica M.; Wilfond, Benjamin S.; Lewis-Newby, Mithya; et al. (Frontiers in Pediatrics, 2022)
Technological advancements and rapid expansion in the clinical use of extracorporeal life support (ECLS) across all age ranges in the last decade, including during the COVID-19 pandemic, has led to important ethical considerations. As a costly and resource intensive therapy, ECLS is used emergently under high stakes circumstances where there is often prognostic uncertainty and risk for serious complications. To develop a research agenda to further characterize and address these ethical dilemmas, a working group of specialists in ECLS, critical care, cardiothoracic surgery, palliative care, and bioethics convened at a single pediatric academic institution over the course of 18 months. Using an iterative consensus process, research questions were selected based on: 1) frequency, 2) uniqueness to ECLS, 3) urgency, 4) feasibility to study, and 5) potential to improve patient care. Questions were categorized into broad domains of societal decision-making, bedside decision-making, patient and family communication, medical team dynamics, and research design and implementation. A deeper exploration of these ethical dilemmas through formalized research and deliberation may improve equitable access and quality of ECLS-related medical care.